Pengaruh Ukuran Perusahaan, Leverage dan Struktur Modal Terhadap Kinerja Keuangan Perusahaan (Studi Pada Perusahaan Manufaktur Sektor Aneka Industri Tahun 2012-2016) - Jessica Talenta Agustina Tambunan; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2018)
Financial performance analysis is performed to measure the achievement of the company from the financial side.This study aimed to test the influence of firm size, leverage and capital structure, either partially or simultaneously, to company financial performance on manufacturing company Miscellaneous Industries sector listed on the Indonesia Stock Exchange period 2012-2016. The data used in this analysis is the is the reference point secondary data in the form of financial report published by IDX. The sample in this study were 36 companies. Data Analysis technique used in this research are simple and multiple linear regression. Results of the study stated that leverage effect significantly to company financial performance, firm size and capital structure are not effect significantly to company financial performance, and simultaneously there was significant influence between firm size, leverage and capital structure to company financial performance.